Reorienting: Looking East - Cooke, Lynne; Third Eye Centre, Glasgow; Nicola Jacobs Gallery, London (Glasgow : Third Eye Centre, 1990)
Boltanski, Christian ; Charlesworth, Sarah ; Hirokawa, Taishi ; Kessler, Jon ; Miyajima, Tatsuo ; Morimura, Yasumasa ; Rousse, Georges ; Sugimoto, Hiroshi
Reorienting: Looking East, Third Eye Centre, Glasgow, 20 January to 4 March 1990 / Nicola Jacobs Gallery, London, 14th March to 22 April 1990
boek